2015
DOI: 10.1051/0004-6361/201525636
|View full text |Cite
|
Sign up to set email alerts
|

Formation of terrestrial planets in disks evolving via disk winds and implications for the origin of the solar system’s terrestrial planets

Abstract: Context. Recent three-dimensional magnetohydrodynamical simulations have identified a disk wind by which gas materials are lost from the surface of a protoplanetary disk, which can significantly alter the evolution of the inner disk and the formation of terrestrial planets. A simultaneous description of the realistic evolution of the gaseous and solid components in a disk may provide a clue for solving the problem of the mass concentration of the terrestrial planets in the solar system. Aims. We simulate the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 47 publications
(69 reference statements)
2
27
0
Order By: Relevance
“…Observations have revealed that the typical lifetime of protoplanetary disks is several million years (Myr) (e.g., Haisch et al 2001;Mamajek 2009;Yasui et al 2010;Takagi et al 2014). Their evolution and dispersal is crucial for the planet formation in protoplanetary disks: for example, the growth of solid particles and the migration of (proto)planets depend on the disk properties (e.g., Matsuyama et al 2003;Ogihara et al 2015;Kobayashi & Tanaka 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Observations have revealed that the typical lifetime of protoplanetary disks is several million years (Myr) (e.g., Haisch et al 2001;Mamajek 2009;Yasui et al 2010;Takagi et al 2014). Their evolution and dispersal is crucial for the planet formation in protoplanetary disks: for example, the growth of solid particles and the migration of (proto)planets depend on the disk properties (e.g., Matsuyama et al 2003;Ogihara et al 2015;Kobayashi & Tanaka 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, no mechanism capable of suppressing Type I migration over the whole inner disk has ever been found. Recent studies have shown that MRI-driven disk winds, in which gas material is blown away from the surface of the disk, can alter the density profile of the gas disk, potentially slowing down or even reversing the migration of the protoplanets (e.g., Suzuki & Inutsuka 2009;Suzuki et al 2010;Ogihara et al 2015). This possibility, however, requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Each formula is given by Eqs. (11)−(13) in Ogihara et al (2015). In addition, the corotation torque decreases as the planet eccentricity increases (e.g., Bitsch & Kley 2010).…”
Section: Damping For Embryosmentioning
confidence: 99%
“…v K ,(28)where b t1 is the migration constant, which depends on the distribution of the temperature and gas surface density of the CJD (see Eq. (10) ofOgihara et al (2015)). If b t1 is negative or positive, the satellite migrates inward or outward, respectively.…”
mentioning
confidence: 99%